1973
DOI: 10.1139/v73-011
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements in the Diterpenoid Series. I. The Solvolysis of Methyl 15β-tosyloxy-13-isopropyl-17-noratis-13-en-18-oate

Abstract: The synthesis o f methyl 15~-hydroxy-l3-isopropyl-17-noratis-13-en-18-oate (14b) is described. Compound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1973
1973
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A cyclic transition state, in which the C14,ß-proton is transferred to the departing sulfonate group, was proposed for this pyrolytic elimination. In the enantiomeric series, A YER and DESHPANDE have achieved a similar rearrangement of an atisane-like diterpene tosylate in which the two carbon bridge (C13-C14) is unsaturated (368). The success of this rearrangement was attributed to charge delocalization by the d 13 double bond in the transition state.…”
Section: ~ Coh (283)mentioning
confidence: 93%
See 2 more Smart Citations
“…A cyclic transition state, in which the C14,ß-proton is transferred to the departing sulfonate group, was proposed for this pyrolytic elimination. In the enantiomeric series, A YER and DESHPANDE have achieved a similar rearrangement of an atisane-like diterpene tosylate in which the two carbon bridge (C13-C14) is unsaturated (368). The success of this rearrangement was attributed to charge delocalization by the d 13 double bond in the transition state.…”
Section: ~ Coh (283)mentioning
confidence: 93%
“…Since the initial suggestion that the aconane skeleton is biogenetically derived from an atisane precursor (363)(364)(365), there have been a number of attempts to effect the proposed Cg-+Cts rearrangement (366)(367)(368). PELLETIER and ICHIHARA first reported that 15-hydroxy-17-noratisane derivatives undergo rearrangement ofthe ethanobridge (C13-Ct4), instead of the C9 -Cs bond (as in 292), regard1ess of the configuration of the hydroxyl group (366).…”
Section: ~ Coh (283)mentioning
confidence: 99%
See 1 more Smart Citation
“…Acid-catalyzed cleavage, however, provided conclusive proof for the presence of a cyclopropane ring. Treatment with HC1 gave a substance C21H33O2CI (43) (mass spectrum) which displayed a one-proton peak in the vinyl region similar to that of 39 itself and a broadened one-proton singlet at 4.46 ppm (W1/2 = 6 Hz) assignable to H-14. This is the result of cyclopropane ring cleavage in such a manner so as to form the most stable carbonium ion, in this instance an allylic carbonium ion.…”
Section: Solvolytic Rearrangement Of Bicyclo[211]hexanolmentioning
confidence: 99%